2014
DOI: 10.1248/bpb.b13-00818
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Recognition of Toxic Advanced Glycosylation End Products through the Macrophage Surface-Receptor Nucleolin

Abstract: Advanced glycosylation end-products (AGEs) are non-enzymatically glycosylated proteins that play an important role in several diseases and aging processes, including angiopathy, renal failure, diabetic complications, and some neurodegenerative diseases. In particular, glyceraldehyde (GCA)-and glycolaldehyde (GOA)-derived AGEs are deemed toxic AGEs, due to their cytotoxicity. Recently, the shuttling-protein nucleolin has been shown to possess scavenger receptor-activity. Here, we investigated whether or not mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…We recently reported that nucleolin is a phagocytic receptor that initiates the removal of a variety of discarded elements. [10][11][12][13] These previous observations and the present study support our hypothesis that cell surface-expressed nucleolin on phagocytes has a general scavenger-like ability.…”
Section: Phagocytosis Of Acldl By Macrophagessupporting
confidence: 92%
See 4 more Smart Citations
“…We recently reported that nucleolin is a phagocytic receptor that initiates the removal of a variety of discarded elements. [10][11][12][13] These previous observations and the present study support our hypothesis that cell surface-expressed nucleolin on phagocytes has a general scavenger-like ability.…”
Section: Phagocytosis Of Acldl By Macrophagessupporting
confidence: 92%
“…12) Taken together, these findings suggest that the polyanionic nature of AcLDL might play a major role in its binding to nucleolin. However, as the binding of rNUC284 and AcLDL did not dissociate with NaCl treatment in SPR analysis (data not shown), factors other than negative charge might also contribute to the binding affinity of nucleolin for AcLDL.…”
Section: Dnamentioning
confidence: 83%
See 3 more Smart Citations